The acute scrotum in childhood and adolescence - Günther, Patrick; Rübben, Iris (Deutsches Ärzteblatt, 2012)
The acute scrotum in childhood or adolescence is a medical emergency (1, 2). The acute scrotum is defined as scrotal pain, swelling, and redness of acute onset (Figure 1). Because the testicular parenchyma cannot tolerate ischemia for more than a...